The Effect of ESG Implementation and Operational Efficiency on Company Performance at PT. Agrojaya Perdana: Pengaruh Penerapan ESG dan Efisiensi Operasional Terhadap Kinerja Perusahaan pada PT. Agrojaya Perdana - Carissa; Linda Wahyu Marpaung (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to determine the effect of ESG implementation on company performance at PT. Agrojaya Perdana, determine the effect of operational efficiency on company performance at PT. Agrojaya Perdana, and determine the effect of ESG implementation and operational efficiency on company performance at PT. Agrojaya Perdana. The research methodology used is quantitative research. The type of data used in this study is quantitative data, which is data obtained in the form of numbers or figures. The data source is primary data. Primary data was obtained from the results of a questionnaire distributed to PT. Agrojaya Perdana employees. The population in this study was PT. Agrojaya Perdana employees. From the population, a sample of 30 was selected. Validity tests, reliability tests, multiple linear regression analysis, classical assumption tests, partial hypothesis tests (T-tests) and simultaneous significance (F-tests), as well as coefficient of determination tests were all included in the data analysis and testing. The results of the analysis provide the equation Company Performance = 6.205 + 0.254 ESG Implementation + 0.548 Operational Efficiency + e. The t-test results show that the ESG implementation variable has a positive and significant effect on company performance at PT. Agrojaya Perdana where tcount (2.043) > ttable (2.000), the operational efficiency variable has a positive and significant effect on company performance at PT. Agrojaya Perdana where tcount (5.980) > ttable (2.000), the F-test results show that Fcount (71.780) > Ftable (3.15) which means that the independent variables (ESG implementation and operational efficiency) simultaneously affect the dependent variable (company performance). The results of the coefficient of determination (R2) show that 70.5% of company performance variables are influenced by ESG implementation and operational efficiency while the remaining 29.5% are influenced by other variables.